Visual skills of the female athletes in team and individual Sports - Mohammadi, N.; Rostami, R.; Alborzi, M. (Annals of Applied Sport Science, 2016)
Visual has always been recognized as one of the most important sensory systems involved in the implementation of many athletic skills because of the close and necessary relationship with performing the movements, and it is considered particularly important by specialists in learning and motor control. Today, in addition to assessing the key indices in athletic performance (physical, medical, psychological and nutritional evaluations), visual skills assessment is also held in great importance. In this regard, the present study aims to answer the question of whether the difference between the visual skills of athletes (team and individual) and non-athletes is significant. For this purpose, 85 subjects (44 non-athletes, 22 athletes in team sports, and 19 athletes in individual sports) participated in this study and were selected using purposive sampling. The research instrument was "sports vision tests of Wilson and Falkel (2004)". The psychometric properties of this test were studied and confirmed through the correlation between the referees and retest method. The results of the statistical analyses showed that there were significant differences between focusing (P<0.001), tracking (P<0.001), sequencing (p=0.009), eye-hand coordination (P<0.001), and vergence (P=0.015) of all-girl teams and individual sports athletes with non-athletes. Just as female individual and team sports athletes were better at focusing and tracking than non-athletes, individual sports athletes were better in vergence, team sports athletes were better in sequencing, and non-athletes were better in eye-hand coordination. However, in regards to visualization, no significant difference was observed between the three groups. According to the results, participation in sports activities, regardless of the type of activity, helps an individual to obtain better abilities in the visual system and its skills. Additionally, the role of visual skills in individual and team fields is different; therefore, due to the importance of vision, it is recommended that coaches consider special planning along with other motor capabilities.